Assessment of Evidence‐Based Standards in the Treatment of Advanced Prostate Cancer in a Community Practice. Issue 3 (May 2017) - Pilon, Dominic; Ellis, Lorie A.; Behl, Ajay S.; Gozalo, Laurence; Emond, Bruno; Lefebvre, Patrick; Calabrese, Renee; Prime, Hilary; Gaylis, Franklin
Abstract : Introduction: : Although the monitoring of patients with advanced prostate cancer is essential to optimize treatment, little is known about adherence to guidelines. In this study we compared testing practices at an integrated urology/radiation oncology group practice with evidence‐based guidelines and best practices. Methods: : Electronic medical records up to December 2014 from the integrated urology/radiation oncology group practice were queried to identify patients who received androgen deprivation therapy and in whom advanced disease was staged as androgen deprivation therapy sensitive, subcastration resistant (incompletely defined probable castration resistant prostate cancer) or castration resistant after April 2011 and for 6 months or more. Frequency of prostate specific antigen and testosterone level testing as well as imaging (magnetic resonance imaging, computerized tomography, positron emission tomography/computerized tomography, bone scan or x‐ray) was evaluated, and compared to national guidelines and best practices. Results: : Overall 346 patients with androgen deprivation therapy sensitive prostate cancer, 90 with subcastration resistant prostate cancer and 102 with castration resistant prostate cancer met the study inclusion criteria. On average, prostate specific antigen was tested every 4.7, 3.7 and 3.3 months for patients with androgen deprivation therapy sensitive disease, subcastration resistant prostate cancer and castration resistant prostate cancer, respectively, compared with the 3 to 12 months and 3 months recommendations of the National Comprehensive Cancer Network and RADAR (Prostate Cancer Radiographic Assessments for Detection of Advanced Recurrence) for patients with androgen deprivation therapy sensitive disease and nonmetastatic castration resistant prostate cancer, respectively. Testosterone levels were assessed within 6 months of classification for 23% and 46% of patients with subcastration resistant prostate cancer and castration resistant prostate cancer, respectively. Finally, 28% and 46% of patients with subcastration resistant prostate cancer and castration resistant prostate cancer, respectively, underwent some type of imaging within 6 months. Conclusions: : This retrospective study of patients receiving androgen deprivation therapy at a particular integrated urology/radiation oncology group practice demonstrated adherence to prostate specific antigen best practices. However, there was some room for improvement in terms of testosterone testing and imaging.